Analisis Retorika Profetik dalam Pidato Dedi Mulyadi dan Relevansinya dengan Pembelajaran Menulis Teks Pidato Kelas VIII - Wulandari, Tania Eka; Hardiyanto, Fahrudin Eko (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2025)
Society needs prophetic rhetoric in everyday life to gain knowledge. Rhetoric is used in various fields, such as politics, economics, education, arts, and journalism, through the use of language that is persuasive, seductive, or persuasive. This study aims to identify prophetic rhetoric in Dedi Mulyadi's speech on YouTube and its implications for teaching speech writing to eighth-grade junior high school students. The method used is qualitative descriptive with data collection techniques involving free listening and conversation. Prophetic rhetoric in Dedi Mulyadi's speeches was chosen as teaching material because it provides a contextual and inspirational learning approach, thereby increasing student engagement in meaningful speech writing. The results of the study indicate that the prophetic rhetoric in these speeches contains the values of ethos, pathos, logos, humanization, liberation, and transcendence, conveyed in straightforward and communicative language. These values are implemented in learning through speech video analysis, value discussions, and the practice of writing locally-themed speeches. The implications of this prophetic rhetoric-based learning successfully create an inspiring and reflective learning environment, encouraging eighth-grade students to actively express their ideas and life values in their speech texts.